Development of a Visual Attention Game Using Difference Detection Mechanics: Design and Usability Evaluation - Bambang Robi'in; Wahyu Pujiyono; M. Bobbyzal Cendana Ze (Journal of Novel Engineering Science and Technology, 2026)
The increasing use of mobile devices has led to the widespread adoption of digital games as interactive systems. However, most mobile games are primarily designed for entertainment and rarely incorporate structured interaction mechanisms to support cognitive training. This study presents the design and development of a visual attention-based mobile game that uses difference-detection mechanics as its core interaction model. The game, named FindX, was developed using the Game Development Life Cycle (GDLC) framework, including initiation, pre-production, production, and testing stages, and implemented using the Unity engine on the Android platform. The system incorporates structured gameplay elements, including progressive difficulty levels, time constraints, and penalty mechanisms for incorrect interactions, to encourage focused visual processing. Functional testing was conducted using a black-box approach to ensure system reliability. Expert evaluation using the Learning Object Review Instrument (LORI) was performed to assess media quality and content suitability. In addition, usability testing was conducted with 23 participants using the System Usability Scale (SUS). The results indicate that the system achieved a media quality score of 80% and a content feasibility score of 93.3%. The usability evaluation produced an average SUS score of 74.1, categorized as Good and Acceptable. These findings indicate that the proposed system is functional, of good media and content quality, and user-friendly, providing a usable interactive environment designed to support visual attention training through structured game mechanics. Efficacy in improving visual attention was not measured in this study and is identified as future work.